The Neuroprotector Benzothiazepine CGP37157 Extends Lifespan in C. elegans Worms - García-Casas, Paloma; Arias-del-Val, Jessica; Alvarez-Illera, Pilar; Wojnicz, Aneta; de los Ríos, Cristobal; Fonteriz, Rosalba I.; Montero, Mayte; Alvarez, Javier (Frontiers in Aging Neuroscience, 2019)
The benzothiazepine CGP37157 has shown neuroprotective effects in several in vitro models of excitotoxicity involving dysregulation of intracellular Ca2+ homeostasis. Although its mechanism of neuroprotection is unclear, it is probably related with some of its effects on Ca2+ homeostasis. CGP37157 is a well-known inhibitor of the mitochondrial Na+/Ca2+ exchanger. However, it is not very specific and also blocks several other Ca2+ channels and transporters, including voltage-gated Ca2+ channels, plasma membrane Na+/Ca2+ exchanger and the Ca2+ homeostasis modulator 1 channel (CALHM1). In the present work, we have studied if CGP37157 could also induce changes in life expectancy. We now report that CGP37157 extends C. elegans lifespan by 10-15% with a bell-shaped concentration–response, with high concentrations producing no effect. The effect was even larger (25% increase in life expectancy) in worms fed with heat-inactivated bacteria. The worm CGP37157 concentration producing maximum effect was measured by HPLC-MS/MS and was close to the IC50 for inhibition of the Na+/Ca2+ exchanger. CGP37157 also extended the lifespan in eat-2 mutants (a model for caloric restriction), suggesting that caloric restriction is not involved in the mechanism of lifespan extension. Actually, CGP37157 produced no effect in mutants of the TOR pathway (daf15/unc24) or the insulin/IGF-1 pathway (daf-2), indicating that the effect involves these pathways. Moreover, CGP37157 was also ineffective in nuo-6 mutants, which have a defect in the mitochondrial respiratory chain complex I. Since it has been described that neuroprotection by this compound in cell cultures is abolished by mitochondrial inhibitors, this suggests that life extension in C. elegans and neuroprotection in cell cultures may share a similar mechanism involving mitochondria.